Development of a Three-Dimensional Media Simulation Game Model to Develop Children's Morals in Kindergarten: A Preliminary Study - St. Maria Ulfah; Muharram; Parwoto (Formosa Journal of Multidisciplinary Research, 2024)
Learning media development is a way to solve an early childhood learning problem in improving children's moral behavior. The purpose of this study was to determine the needs of teachers in developing a three-dimensional media simulation game model in kindergarten to improve children's moral aspects. The method used in this research is a qualitative method using interviews and observations as research instruments. There are several important points in the findings of this study, namely (1) children's moral abilities are still lacking, (2) the ability of teachers to package material about children's morals in kindergarten is also lacking, and (3) teachers need a game model for children that is interesting and fun. Therefore, it is necessary for teachers to design a three-dimensional media simulation game model that can improve children's moral abilities.